AB1325-HPR THE TRANSITION FROM PEDIATRIC TO ADULT RHEUMATOLOGY OF 347 PATIENTS AT A SINGLE CENTER. (2nd June 2020) - Ugurlu, S.; Egeli, B. H.; Adrovic, A.; Barut, K.; Sahin, S.; Yildiz, M.; Kasapcopur, O.; Ozdogan, H.
Abstract : Background: Pediatric to adult rheumatology transition can be a challenge for both the patient and the clinician, especially in rheumatology as it includes chronic diseases with close follow-up. Objectives: The objective of this study is to understand our tertiary rheumatology center patient demographic transitioning from pediatric to adult rheumatology in order to design prospective studies enhancing the evidence of transition recommendations. Methods: Patients included in this study are regularly followed-up in our adult rheumatology clinic and were regularly followed up in our pediatric rheumatology clinic in the past. They were all diagnosed with a rheumatologic condition receiving treatment. The patient files were assessed to have a better understanding of their demographic, disease and treatment information. Results: Our cohort includes 347 patients diagnosed with a variety of conditions that are Familial Mediterranean Fever (FMF) (n=216), Juvenile Idiopathic Arthritis (JIA) (n=56), Juvenile Spondyloarthritis (jSPA) (n=39), Systemic Lupus Erythematosus (SLE) (n=20), Behçet's Disease (n=7) and the rest of the rheumatologic conditions with less than 5 patients each. The mean age of the patients during transition, mean age of diagnosis, and follow-up duration are 21.34±1.7, 10.4±4.18, and 10.82±4.4 in respective order. The treatment regimens the patients received are summarized in Table 1 . Seven patients had FMF related attacks. In addition to attacks, one FMF patient had bilateral ankle pain and one patient had leg pain. One patient out of three diagnosed with Takayasu's disease was still symptomatic. One patient had uveitis-related symptoms. One patient diagnosed with SLE had skin dryness. Furthermore, there were patients with sequelae formation. One patient diagnosed with oligoarticular JIA (oJIA) had bilateral hip sequela with the additional left hip prosthesis. One oJIA patient had micrognathia, and one had left knee sequela. One pJIA patient had small joint sequelae. One sJIA patient had bilateral hip sequelae. One jSPA patient had enthesopathy. One FMF patient had proteinuria due to amyloidosis formation. Another FMF patient had hip surgery due to sequela. Conclusion: Our center had patients with a variety of conditions with different natures of diseases. EULAR recommends the transition process to start no later than 14 years of age; however, this process started at the mean age of 21 in our patients. In most of these patients, especially the ones diagnosed with FMF, the control of disease activity was maintained. The transition of these different clinical entities might require certain amendments to the standard of care. For future references, we will be able to understand more about the adulthood prognosis of these clinical entities. Disclosure of Interests: None declared